Angular correlations and CP asymmetries in the decay Φ → ZZ → 4 fermions - Kovalchuk, V.A. (Вопросы атомной науки и техники, 2009)
We investigate the possibility of detecting effects of CP violation in the process Φ → ZZ → 4 fermions for a most general of Φ ZZ coupling of a Higgs boson with a spin zero with a pair of Z bosons. Moreover, as the amplitude of the Φ → ZZ decay we used its representation in terms of the linear polarization of the vector bosons. We have considered asymmetries that can be signal of CP violation and have estimated their sizes. It is shown, that measurement of angular correlations is important both for the test of the Standard Model, and for search of effects of new physics at the TeV scale. Мы исследуем возможность обнаружения эффектов CP-нарушения в процессе Φ → ZZ → 4 фермиона для самого общего Φ ZZ-взаимодействия хиггсовского бозона с нулевым спином с парой Z-бозонов. Причем, в качестве амплитуды распада Φ → ZZ мы использовали её представление посредством линейно поляризационных состояний векторных бозонов. Мы рассмотрели асимметрии, которые могут быть сигналом CP-нарушения и оценили их величины. Показано, что измерение угловых корреляций является важным как для проверки предсказаний стандартной модели, так и для поиска эффектов "новой физики" в ТэВ-ном масштабе. Ми досліджуємо можливість виявлення ефектів CP-порушення у процесі Φ → ZZ → 4 ферміона для найбільш загальної Φ ZZ-взаємодії хігсівського бозона з нульовим спіном з парою Z-бозонів. Причому, у якості амплітуди розпаду Φ → ZZ ми використали її подання за допомогою лінійно поляризаційних станів векторних бозонів. Ми розглянули асиметрії, які можуть бути сигналом CP-порушення та оцінили їхні величини. Показано, що вимір кутових кореляцій є важливим як для перевірки передбачень стандартної моделі, так і для пошуку ефектів "нової фізики" в ТеВ-ному масштабі.